Are horticultural exports a replicable success story?: evidence from Kenya and Côte d’Ivoire - Minot, Nicholas; Ngigi, Margaret (International Food Policy Research Institute, 2004)
Kenyan horticultural exports are often cited as a success story in African agriculture. Fruit and vegetable exports from Côte 'Ivoire have received less attention, but the export value is similar to that of Kenya. This paper focuses on three questions. First, do the horticultural sectors of Kenya and Côte d'Ivoire constitute valid success stories? Second, what factors have contributed to the success (or lack thereof)? And third, to what degree can the success be replicated in other African countries? The paper finds that Kenyan horticultural exports are indeed a success story: horticulture has become the third largest earner of foreign exchange, more than half the exports are produced by smallholders, and smallholders gain from producing for the export market. At the same time, the total number of smallholders producing for export is relatively small, and trends in European retailing may shift the advantage to larger producers. Côte d'Ivoire is not as clearly a success story because the most of the exports are produced on large industrial estates and because growth has been uneven. Ivorian exports rely on preferential access to European markets relative to Latin American exporters, raising doubts about sustainability. Factors in the growth and success of horticultural exports include a realistic exchange rate, stable policies, a good investment climate, competitive international transport connections, institutional, and social links with markets in Europe, and continual experimentation with the market institutions to link farmers and exporters. Smallholder participation is encouraged by farmer training and extension schemes, investment in small-scale irrigation, and assistance in establishing links with exporters. Many of the lessons of Kenyan horticulture can be applied elsewhere in Africa. Indeed, Kenya faces increasing competition from neighboring countries trying to replicate its success. At the same time, market institutions take time to develop, and demand constraints probably prevent other African countries from achieving the same level of success as Kenya.